2016
DOI: 10.1097/md.0000000000005241
|View full text |Cite
|
Sign up to set email alerts
|

Brahma-related gene 1 induces apoptosis in a p53-dependent manner in human rheumatoid fibroblast-like synoviocyte MH7A

Abstract: Blocked apoptosis and aggressive inflammatory responses occur in fibroblast-like synoviocyte (FLS) of rheumatoid arthritis (RA) patients. Although Brahma-related gene 1 (BRG1) is considered as a tumor suppressor, few research covers its role in RA. This study aims to reveal effects and potential mechanisms of BRG1 in human FLS cell line MH7A.BRG1 expression in MH7A cells was altered by transfection of overexpression vectors or short hairpin RNAs (shRNAs). Cell viability and apoptosis were detected by 3-(4,5-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…CRSwNP can be, however, compared to other in ammatory processes. Hou and Xing found increased expression levels of p53, CASP3 and CASP9 and decreased expression levels of Bcl-2 in patients with RA 51 . Our results suggest a similar in ammation pattern.…”
Section: Discussionmentioning
confidence: 98%
“…CRSwNP can be, however, compared to other in ammatory processes. Hou and Xing found increased expression levels of p53, CASP3 and CASP9 and decreased expression levels of Bcl-2 in patients with RA 51 . Our results suggest a similar in ammation pattern.…”
Section: Discussionmentioning
confidence: 98%
“…CRSwNP can be, however, compared to other inflammatory processes. For example, Hou et al found increased expression levels of P53 , CASP3 , and CASP9 and decreased expression levels of BCL-2 in patients with rheumatoid arthritis (RA) [ 51 ]. Our data corroborate this gene expression pattern and suggest a convergent molecular mechanism of apoptosis activation.…”
Section: Discussionmentioning
confidence: 99%
“…Hou et al. revealed that SMARCA4 induces apoptosis of human rheumatoid fibroblast-like synoviocyte MH7A cells in a p53-dependent pattern ( 48 ). Therefore, consistent with the results of these previous studies, our study confirms the important role of SMARCA4 in the pathogenesis of RA.…”
Section: Discussionmentioning
confidence: 99%